FENOMENA KEHIDUPAN SOSIAL MASYARAKAT DALAM SENI LUKIS SOCIETY SOCIAL LIFE PHENOMENON IN PAINTING - BURHANI ANAS, Drs. Idran Wakidi, Drs. Ajusril S (Serupa The Journal of Art Education, 2014)
Not all people are lucky in life. Not a few who live with limitations, alienatedfrom the environment and even neglected. Faced with a prolonged economic crisis, social in equality and the development of technology, gave birth to conflicts in life. The author tried to illustrate this problem in a surrealistic contemporary painting. Contemporary art is no longer considering the ethics pre-existing. The creation from the idea to a work of art, passing through along process and a lot of observation. From this main ideas or general idea, will be developed into ten itles of paintings,such as: 1) "The Forgotten", 2) "Consequences", 3) "Controlled by Era", 4) "Street Children", 5) "Children Exploitation", 6)" Chasing a Dream", 7)" Don’t Call Them Waste of Society", 8)" Indecision", 9)" Hedonism(Adore Luxury) ", 10)"Wasted Dream". Each work displayed is a picture of the conflict and the occured phenomenon in living human’s life.Keywords: conflict, social life, art of painting.